PENERAPAN METODE NUMBERED HEADS TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR GERAK PADA BENDA BAGI SISWA KELAS VIII SMPN 1 KARANGPLOSO - Lilik Fauzia (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2016)
This study aims to improve student learning outcomes in terms of cognitive, affective, and psychomotor using NHT. This study is a classroom action research conducted in three cycles. This study assigned the VIII graders of SMPN 1 Karangploso Malang in 2013.  The results showed that (1) application of learning model using Numbered Heads Together increases student activities. Respectively, rate percentage of circle 1 to circle 3 is 69.35%, 76.61%, and third cycle of 87.58%; (2) the increased subject matters include motion on the body, basic competence to understand rectilinear motion and the influence of the force of the motion based on Newton's law, and its application in motion living beings and the motion of objects in everyday life.